Ujaran kebencian pada ruang – ruang digital (Jurnal Kajian Media, 2020)
Today, advances in information and communication technology are rapidly showing that technology can make sustainable change for society and create diversity in the media. This is evidenced by changes in the availability of media that are historically scarce and limited access to the availability of outlets or media that are abundant. New media options are offered to audiences to channel their emotions. Citizen journalism, which is never as difficult as in the digital era, has become more diverse in terms of expression from citizens, such as the presence of hate speech. This term is being channeled through social media into the digital public space by people. So, enliven the digital public space before the information is inevitably disrupted. The current situation is changing from public satisfaction to group or individual satisfaction from joint hearings. Researchers see this empirical phenomenon as very important to study. Its purpose is to reveal how hatred is expressed in the digital age. The aim of this research is to express hatred in social media. This research shows that social media, a global public space, has been used by people to communicate their thoughts in several attempts. There is a community journalism philosophy, and there are common reasons for voicing hatred.Keywords: hoax; public sphere; digital; social media